1999
DOI: 10.1016/s1074-7613(00)80005-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Th1 Activity and Development of Chronic Enterocolitis in Mice Devoid of Stat3 in Macrophages and Neutrophils

Abstract: We have generated mice with a cell type-specific disruption of the Stat3 gene in macrophages and neutrophils. The mutant mice are highly susceptible to endotoxin shock with increased production of inflammatory cytokines such as TNF alpha, IL-1, IFN gamma, and IL-6. Endotoxin-induced production of inflammatory cytokines is augmented because the suppressive effects of IL-10 on inflammatory cytokine production from macrophages and neutrophils are completely abolished. The mice show a polarized immune response tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
870
3
8

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,123 publications
(926 citation statements)
references
References 40 publications
45
870
3
8
Order By: Relevance
“…pSTAT3, which has antagonistic effect on pSTAT1 (27,28), plays a key role in suppressing the function of neutrophils, NK cells, DCs (31)(32)(33) and negatively regulating the Th1-mediated inflammatory response (30,31). Therefore, the balance of pSTAT1 and pSTAT3 plays an important role in regulating immune response and maintaining immunohomeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pSTAT3, which has antagonistic effect on pSTAT1 (27,28), plays a key role in suppressing the function of neutrophils, NK cells, DCs (31)(32)(33) and negatively regulating the Th1-mediated inflammatory response (30,31). Therefore, the balance of pSTAT1 and pSTAT3 plays an important role in regulating immune response and maintaining immunohomeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…pSTAT3, which has antagonistic effect on pSTAT1 (27,28), is not only a potent negative regulator of the Th1-mediated inflammatory response, but also an activator of many genes that are crucial for immune regulation (29,30). Down-regulation of STAT3 could enhance Th1 type immune response and activate DCs, NK cells and macrophages (31)(32)(33). So the balance of pSTAT1 and pSTAT3, which has been studied in cancer immunity (31,34), has an important role in regulation of immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in data not shown, we demonstrate by chromatin immunoprecipitation that STAT-1 is physically associated with the IL-10 promoter at 16 h but not at 1 h following LPS challenge. Heterodimerization of STAT-1 with STAT-3 to mediate in vivo repression of IL-10 expression may play a role in the regulation of IL-10, as mice lacking STAT-3 in myeloid cells also overproduce IL-10 in response to LPS injection [29]. However, it is also possible that the observed effect is due to a different STAT that is activated in the course of LPS response only in the absence of STAT-1.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of STAT3 has been shown to increase sensitivities to apoptosis and certain defect in wound healing. Takeda et al [62] also deleted the STAT3 gene from macrophages and neutrophils by using the macrophagespecific lysozyme promoter. STAT3 ablation in these mice results in an increased sensitivity to endotoxin/LPS shock, chronic inflammation and chronic enterocolitis with age.…”
Section: Stat3 Initiation Of Inflammation and Mammalian Disorders Inmentioning
confidence: 99%
“…When IL-10-deficient mice are raised under germ-free conditions, IBD does not occur, indicating the importance of innate interactions. A seminal finding by Akira's group revealed that STAT3 is the mediator of IL-10 for immune suppression [62]. However, the detailed mechanism is unclear.…”
Section: Ibdmentioning
confidence: 99%